1979
DOI: 10.1136/thx.34.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural artefacts in biopsied normal myocardium and their relevance to myocardial biopsy in man.

Abstract: Biopsy specimens, as a source of myocardial tissue, are being used increasingly in the appraisal of various myocardial diseases. A study of myocardial tissue, biopsied and processed in various ways, and obtained from normal healthy experimental animals, showed that a variety of artefacts may be found. These artefacts develop in reactive, beating myocardium but not in non-reactive hearts. The artefacts are in many instances similar to, or mimic, changes previously described as pathological in origin. This is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Patient I also had Wolff-ParkinsonWhite syndrome, and patient 13 In 50% of the patients in this study, the biopsy specimens showed changes characteristic of a nonspecific cardiomyopathy, which are indistinguishable from alterations seen in biopsy specimens from patients with idiopathic, dilated, congestive cardiomyopathy. 1' 7 Despite the severity of the histologic abnormalities, heart size, resting cardiac function, and exercise tolerance were well-preserved in these patients.…”
Section: Resultsmentioning
confidence: 52%
“…Patient I also had Wolff-ParkinsonWhite syndrome, and patient 13 In 50% of the patients in this study, the biopsy specimens showed changes characteristic of a nonspecific cardiomyopathy, which are indistinguishable from alterations seen in biopsy specimens from patients with idiopathic, dilated, congestive cardiomyopathy. 1' 7 Despite the severity of the histologic abnormalities, heart size, resting cardiac function, and exercise tolerance were well-preserved in these patients.…”
Section: Resultsmentioning
confidence: 52%
“…Our biopsy material was rarely spoiled by artifacts. We therefore do not share the pessimism of Eckner et al 40 and Olmesdahl et al 41 regarding the problem of bioptome-induced artifacts in the interpretation of endomyocardial biopsy.…”
Section: Reproducibility Of Electron Microscopic Evaluationmentioning
confidence: 99%
“…After desensitisation, the central artefact-free core of the biopsy specimen was removed as described by Olmesdahl et al 33 and diced into 1 mm cubes before re-immersion in fixative for a further 1 hour. After postfixation/staining with 1% osmium tetroxide, the tissue was dehydrated through increasing concentrations of ethanol before being embedded in Spurr epoxy resin.…”
Section: Electron Microscopymentioning
confidence: 99%